Cardioprotective Potential of Plant-Derived Molecules: A Scientific and Medicinal Approach. Issue 2 (24th May 2019) - Shah, Syed Muhammad Ali; Akram, Muhammad; Riaz, Muhammad; Munir, Naveed; Rasool, Ghulam
Since the beginning of human civilization, plants have been used in alleviating the human distress and it was recorded for about thousands of years ago that the plants are being used for medicinal purposes. Natural bioactive compounds called phytochemicals are obtained from medicinal plants, vegetables, and fruits, which functions to combat against various ailments. There is dire need to explore the plant biodiversity for its medicinal and pharmacological potentials. Different databases such as Google scholar, Medline, PubMed, and the Directory of Open Access Journals were searched to find the articles describing the cardioprotective function of medicinal plants. Various substances from a variety of plant species are used for the treatment of cardiovascular abnormalities. The cardioprotective plants contain a variety of bioactive compounds, including diosgenin, isoflavones, sulforaphane, carotinized, catechin, and quercetin, have been proved to enhance cardioprotection, hence reducing the risk of cardiac abnormalities. The present review article provides the data on the use of medicinal plants particularly against cardiac diseases and to explore the molecules/phytoconstituents as plant secondary metabolites for their cardioprotective potential.